What inspires design? [electronic resource] - Video Education Australasia (New York, N.Y. Films Media Group, 2012)
#aWhere do designers get their ideas? How do the environment, culture, and history shape designers' outlooks? Can collaboration create an inspired design? How do inspiration and innovation relate to each other? Modern design, powered by new technology and production techniques, is pushing the limits of human ingenuity. This program allows viewers to explore the minds and methods of product designers to learn how to breathe life into a new idea.
What Is Inspiration? (2:59) -- Sources of Inspiration: Past Innovation and Creativity (4:37) -- Sources of Inspiration: Collaborative Approaches (4:52) -- Inspiration and Innovation (3:22) -- Credits: What Inspires Design? (0:52)
VCD
Keywords: Design; Communication in design; Computer graphics